AI-related risk: The merits of an ESG-based approach to oversight - Mardi Witzel; Niraj Bhargava (Centre for International Governance Innovation (CIGI), 2023)
Artificial intelligence (AI) technology has been found to generate value for many firms; however, it also has unintended and undesirable consequences. The reality of AI-related risk has led to the development of AI governance frameworks and calls for greater oversight of the use of AI. The merits of an ESG (environmental, social, governance)-based approach to oversight of AI-related risk are considered in this paper, with a focus on the current trajectory of international sustainability standards development. Despite their differences, AI governance and ESG reporting both seek to address risk in the broadest sense, with proactive and transparent approaches to its management and mitigation. A preliminary set of recommendations for incorporating material AI-related risk into ESG reporting, covering both general or context-setting disclosures and industry-specific disclosures, is provided.
Keywords: 330